Examinations of Consumers' Reactions towards Advertising Messages. An Example of the Application of Electroencephalography and Selected Biometric Techniques - Wąsikowska , Barbara (Studia Oeconomica Posnaniensia, 2017)
The development of scientific research in the area of psychology and neurobiology, as well as the technological achievements concerning brain imaging methods, have caused the dynamic development of research methods in economic sciences. New disciplines have appeared, such as: behavioural economy, behavioural finance, neuromanagement and neuromarketing. In the article the author focused on the presentation of a marketing study conducted with applying cognitive neuroscience methods and biometric techniques. The aim of the study was a behaviour analysis of consumers watching the advertisements of different products. Research was conducted in two stages. The first part of the study constituted an experiment with the use of different cognitive neuroscience methods and biometric techniques. The second part of the study consisted of direct interviews with respondents. The analysis of the empirical data showed that the application of the methods taken from neuroscience had allowed receiving additional information which supplemented the knowledge that is being acquired from a direct interview.